Changes in Poland`s policy towards German population in the first half of the 1950s = Zmiany w polityce państwa polskiego wobec ludności niemieckiej w pierwszej połowie lat pięćdziesiątych XX wieku - Browarek, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
With the end of the 1940s it occurred that relocations had not entirely solved the problem of the presence of German population in Poland since it had become essential that keeping c. two hundred thousand Germans was necessary for Polish economy. As a result, the question of solving several issues relating to their functioning in Poland appeared. However, it was the change in the international situation which had direct influence on the policy change towards this population - the creation of an allied German country (GDR) and the signing of the Treaty of Görlitz.
Keywords: Germans in Poland; national minorities in Poland; national policy; Niemcy w Polsce; mniejszości narodowe w Polsce; polityka narodowościowa